LGBT cultural competence of healthcare workers in Iloilo - Pulmones, James Angelo S.
This study assesses healthcare providers' level of Cultural Competency in delivering healthcare services to the LGBT patient population. LGBT Cultural Competence is the ability of healthcare organizations and providers to accommodate the health needs and deliver healthcare services to the LGBT patient population (Betancourt et al., 2002; Nowaskie, 2018) LGBT Cultural Competency plays a crucial role in reducing the health disparities experienced by equipping healthcare workers with the necessary knowledge, attitudes, and skills when dealing with LGBT patients. Forty-six (46) participants completed the LGBT-DOCCS survey, assessing their overall LGBT Cultural Competency. Qualitative interviews were conducted with five participants to make sense of the quantitative findings. Results revealed a moderate level of LGBT Cultural Competency among healthcare workers, high attitudinal awareness, moderate competency in clinical preparedness, and low basic knowledge. Thematic analysis identified six main themes that shed light on the context of LGBT Cultural Competence in the country and the level of LGBT Cultural Competency of Healthcare workers in Iloilo. These results infrom efforts to improve LGBT cultural competence and establish an inclusive healthcare system through education, interventions, and training programs for healthcare workers, ultimately ensuring equitable care for patients regardless of their gender or sexual orientation. Future research could refer to this study to unpack other factors that may lead to the understanding and improvement of LGBT cultural competence in the country.